Interpreting weekly external load in professional soccer: A position-based and context-driven approach for the "real world" setting - Gonçalves, L. G.; Silva, R. M.; Moraes-Neto, M. V.; Pasquarelli, B.; Pastor, A.; Plato, F. D. O.; Leitão, R. A. A.; Augusto, D.; Vasconcellos, F.; Aquino, R. (International Journal of Sports Science & Coaching, 2025)
This study analyzed the weekly external load of professional soccer players with two main aims: 1) to describe the external load (i.e. distance and accelerometry-based measures) according to match-contextual difficulty—defined as a scoring system combining match location and the quality of opposition— and playing positions; 2) to compare the external load in contexts of low and high match-contextual difficulty. Eighteen professional soccer players were monitored over 13 weeks using global positioning systems (GPS) units and accelerometers. Players participating for at least 60 min in non-congested weeks were analyzed for total distance, distances covered at various speeds and acceleration levels, and Player Load. Match difficulties were categorized as "high" (score > 10) or "low" (score * 10) and determined using match location and quality of opposition. The results revealed that the highest external loads occurred mid-week (e.g. MD-3), decreasing towards the week's end (e.g. MD-1), with external defenders and midfielders facing higher demands than central defenders and forwards. In low-difficulty scenarios (p < 0.001-0.030), external loads were higher than in high-difficulty scenarios, particularly on days preceding a match (MD-4 and MD-2). Conversely, high-difficulty matches context increased high-speed/sprinting distance and mechanical work on specific days (MD-3 and MD-1) (p < 0.001-0.020). The findings suggest that external load can be increased early in low-difficulty match weeks, while reduced demands are recommended before high-difficulty matches weeks. Coaches should adopt context-approach periodization to appropriately plan physical stimulus throughout the weekly competition.